2023
DOI: 10.21053/ceo.2022.01361
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Guideline: Clinical Efficacy of Nasal Surgery in the Treatment of Obstructive Sleep Apnea

Abstract: Obstructive sleep apnea (OSA) is a common disorder characterized by upper airway obstruction during sleep. To reduce the morbidity of OSA, sleep specialists have explored various methods of managing the condition, including manifold positive airway pressure (PAP) techniques and surgical procedures. Nasal obstruction can cause significant discomfort during sleep, and it is likely that improving nasal obstruction would enhance the quality of life and PAP compliance of OSA patients. Many reliable studies offer ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…However, there is sparse data on if topical medications can improve daytime sleepiness or objective metrics on polysomnography. In contrast, nasal surgery has been shown to improve daytime sleepiness in OSA patients, with evidence demonstrating a significant improvement in postoperative ESS scores [26 ▪ ]. Although isolated nasal surgery alone has not been shown to correct AHI [27], multiple studies have demonstrated that nasal surgery can improve subjective measures nasal obstruction and improve CPAP use and effectiveness [28,29].…”
Section: Nasal Airwaymentioning
confidence: 99%
“…However, there is sparse data on if topical medications can improve daytime sleepiness or objective metrics on polysomnography. In contrast, nasal surgery has been shown to improve daytime sleepiness in OSA patients, with evidence demonstrating a significant improvement in postoperative ESS scores [26 ▪ ]. Although isolated nasal surgery alone has not been shown to correct AHI [27], multiple studies have demonstrated that nasal surgery can improve subjective measures nasal obstruction and improve CPAP use and effectiveness [28,29].…”
Section: Nasal Airwaymentioning
confidence: 99%